Improvement in maize bread quality through addition of pre-gelatinized starch, sourdough in combination with dough sheeting - Taylor, J.R.N. (John Reginald Nuttall) (University of Pretoria, 2016)
Dissertation (MSc)--University of Pretoria, 2016.